Chronic pelvic pain syndrome: Highlighting medicinal plants toward biomolecules discovery for upcoming drugs formulation. (4th December 2019) - Salehi, Bahare; Butnariu, Monica; Corneanu, Mihaela; Sarac, Ioan; Vlaisavljevic, Sanja; Kitic, Dusanka; Rahavian, Amirhossein; Abedi, Amirreza; Karkan, Morteza F.; Bhatt, Indra D.; Jantwal, Arvind; Sharifi‐Rad, Javad; et al.
Abstract : Chronic pelvic pain syndrome (CPPS) can be triggered by a various types of gynecological, gastrointestinal, urological, and musculoskeletal disorders. Recently, the role of the central nervous system has proven to be an integral part on the development of any chronic pain syndrome, including CPPS. However, owing to the complex and heterogeneous etiology and pathophysiology of CPPS, the establishment of effective therapeutic interventions remains challenging for both physicians and patients. Nonetheless, recent studies have pointed that medicinal plants and their secondary metabolites can be effectively used in CPPS therapy, besides contributing to restore the patients' quality of life and potentiate the conventional CPPS management. In this sense, this review aims to provide a careful overview on the biomedical data for the use of medicinal plants use and their secondary metabolites on CPPS management.